IL-33 Gene Polymorphisms as Potential Biomarkers of Disease Susceptibility and Response to TNF Inhibitors in Rheumatoid Arthritis, Ankylosing Spondylitis, and Psoriatic Arthritis Patients - Iwaszko, Milena; Wielińska, Joanna; Świerkot, Jerzy; Kolossa, Katarzyna; Sokolik, Renata; Bugaj, Bartosz; Chaszczewska-Markowska, Monika; Jeka, Sławomir; Bogunia-Kubik, Katarzyna (Frontiers in Immunology, 2021)
Objective Rheumatoid arthritis (RA), ankylosing spondylitis (AS), and psoriatic arthritis (PsA) belong to inflammatory rheumatic diseases, the group of conditions of unknown etiology. However, a strong genetic component in their pathogenesis has been well established. A dysregulation of cytokine networks plays an important role in the development of inflammatory arthritis. Interleukin 33 (IL-33) is a recently identified member of the IL-1 family. To date, the significance of IL-33 in inflammatory arthritis has been poorly studied. This research aimed to investigate the potential of IL-33 gene polymorphisms to serve as biomarkers for disease susceptibility and TNF inhibitor response in RA, AS, and PsA patients. Materials and Methods In total, 735 patients diagnosed with RA, AS, and PsA and 229 healthy individuals were enrolled in the study. Genotyping for three single nucleotide polymorphisms (SNPs) within the IL-33 gene, namely, rs16924159 (A/G), rs10975519 (T/C), and rs7044343 (C/T), was performed using polymerase chain reaction amplification employing LightSNiP assays. Results In the present study, the IL-33 rs10975519 CC genotype was associated with a decreased risk of developing RA in females, while the IL-33 rs16924159 polymorphism was associated with the efficacy of anti-TNF therapy and clinical parameters for RA and AS patients. The IL-33 rs16924159 AA genotype correlated with higher disease activity and worse clinical outcomes in RA patients treated with TNF inhibitors, and AS patients carrying the IL-33 rs16924159 AA genotype had higher disease activity and a worse response to anti-TNF therapy. That indicates a deleterious role of the IL-33 rs16924159 AA genotype in the context of RA, as well as AS. Conclusions The obtained results suggest that IL-33 gene polymorphisms might be potential candidate biomarkers of disease susceptibility and anti-TNF treatment response in patients with inflammatory rheumatic diseases.